Polityka integracyjna Polski a integracja kulturowa społeczności arabskiej w Polsce - Mustafa Switat (Postscriptum Polonistyczne)
The aim of the paper is to present selected aspects of integration (in the cultural sense) of the Arabic community in Poland in the context of Poland’s integration (migration) policy which Poland formally does not have at present. What Arabic and Polish respondents have to say about the integration process may be useful for the more efficient management of the immigration phenomenon.